(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article provides an overview of the concept of Conflict between United States of America and Iran The conflict between Iran and the USA is rooted in a combination of political, ideological, and geopolitical factors. These two countries have had strained relations for several decades, with various incidents and disputes contributing to the ongoing conflict. There are ideological differences between the two countries. Iran is an Islamic republic with a revolutionary ideology, while the USA is a secular democracy. These ideological differences, along with differing geopolitical interests, have further fueled the conflict. It is important to note that the conflict between Iran and the USA is complex issue with multiple dimensions and regional implications.